Two-Dimensional Fredholm Integro-Differential Equation with Singular Kernel and Its Numerical Solutions - Abeer M. Al-Bugami (Advances in Mathematical Physics)
In this paper, we introduce the nonlinear Fredholm integro-differential equation of the second kind with singular kernel in two-dimensional NT-DFIDE. Furthermore, we study this new equation numerically. The existence of a unique solution of the equation is proved. The numerical results of NT-DFIDE are obtained by the following methods: Toeplitz matrix method (TMM) and product Nystrom method (PNM). The given applications showed the efficiency of these methods.